Propuesta de oferta y demanda de productos con madera de melina en el cliente final de la cadena de valor de ASIREA en Pococí, Limón, Costa Rica - Pereira-Ramírez, Keyla Tatiana (Instituto Tecnológico de Costa Rica, 2017)
We are faced with a great need to promote and generate confidence in the use of wood and create industrial plants that include value chains, because the use of wood is a constant decline and is replaced by other structural materials (Barrantes and Ugalde, 2015, Serrano and Moya, 2011). The objective of this study was to evaluate the profitability of the supply of Gmelina arborea (melina) wood-based forest products in the value chain from ASIREA from Limón. The melina yield model elaborated by Murillo (2017) was used to determine the supply of the melina wood. The model indicated the available volume by thinning and by logging. To select the potential melina products, several surveys were conducted to determine the currently market. To define a strategy to offer products with a added value, a simulation of a business model was generated, in which ASIREA would offer services such as sawing, drying and finally, selling the wood to offer greater traceability in the process of production. In addition, a list of possible products to be offered was generated along with the cost of production and sale price. The results of the study suggest that it is feasible for ASIREA to sell wood products that offers products with added value; however it is necessary to determine a real demand for the products to be sold.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2017.
Keywords: Manufactura; Madera; Forestal; Cadenas de valor; Rentabilidad